Asymptotics of the number of standard Young tableaux of skew shape. (May 2018) - Morales, Alejandro H.; Pak, Igor; Panova, Greta
Abstract: We give new bounds and asymptotic estimates on the number of standard Young tableaux of skew shape in a variety of special cases. Our approach is based on Naruse's hook-length formula. We also compare our bounds with the existing bounds on the numbers of linear extensions of the corresponding posets.